RECRUTTER - ASYNCHRONOUS INTERVIEW SYSTEM (CIPEEX, 2022)
IN THIS NEW MODEL OF NETWORK SOCIETY, WHICH IS ALREADY WIDESPREAD THROUGHOUT THE WORLD, PEOPLE AND COMPANIES IN GENERAL ARE LOOKING FOR QUICK, PRACTICAL AND TECHNOLOGICAL SOLUTIONS FOR MOST OF THEIR DAILY PROBLEMS, IN THE CORPORATE WORLD, FOR EXAMPLE, SOLUTIONS THAT OPTIMIZE THE TIME OF PROFESSIONALS ARE ALWAYS WELL REGARDED BY ENTREPRENEURS AND INVESTORS. THIS PROJECT AIMS AT THE STUDY, EVALUATION AND PART OF THE PROTOTYPING OF AN ASYNCHRONOUS INTERVIEW SYSTEM (RECRUTTER), SUCH SYSTEM HAS AS MAIN OBJECTIVE TO STREAMLINE AND OPTIMIZE THE INTERVIEW PROCESS OF COMPANIES, MAKING THE FIRST MOMENT BETWEEN COMPANY AND CANDIDATES AN ASYNCHRONOUS MOMENT, WHERE FROM A RECRUITER'S VIDEO BANK, THE CANDIDATE SENDS A VIDEO WITH THEIR ANSWERS THROUGH RECRUTTER, THIS PROCESS STREAMLINES THE FIRST STAGE OF MOST OF A COMPANY'S SELECTION PROCESSES. FOR THE DESIGN OF THE RECRUTTER SYSTEM, AGILE THINKING METHODOLOGIES WERE USED, THE ENTIRE SYSTEM DEVELOPMENT PROCESS WAS DESIGNED FROM THE SURVEY OF FUNCTIONAL REQUIREMENTS, AND AIMING AT A MINIMUM VIABLE PRODUCT (MVP), WHICH IN GENERAL WILL BE THE SYSTEM WITH THE MODULE OF REGISTRATIONS AND THE BASIC INTERVIEW WORKING. BASED ON THIS MVP, THE DESIGN PROCESS, PERSONAS AND EVEN THE COLOR PALETTE TO BE USED THROUGHOUT DEVELOPMENT WERE DEFINED. THE RESULTS OBTAINED AT THIS STAGE OF DEVELOPMENT ARE SUMMARIZED IN FUNCTIONAL AND NON-FUNCTIONAL REQUIREMENTS, MINIMUM VIABLE PRODUCT, PERSONAS AND SOME STATIC PROTOTYPES OF SOME MODULES THAT WILL BE DEVELOPED FOR THE SYSTEM.